Relationship Between Muscle Tone and Elasticity: Simultaneous Quantitative Assessment Using Train-of-Four Monitoring and Continuous Shear Wave Elastography During Anesthesia Induction—A Prospective Observational Study - Hitoshi Shitara; Tadanao Hiroki; Ren Koda; Tsuyoshi Sasaki; Masataka Kamiyama; Ryosuke Miyamoto; Kurumi Nakase; Fukuhisa Ino; Takuma Kachi; Rie Mieda; Chizu Aso; Yoshiki Yamakoshi; et al. (Diagnostics)
Background/Objectives: Non-invasive evaluations of muscle elasticity and tone are crucial in musculoskeletal medicine. Shear wave elastography (SWE) provides quantitative assessments of muscle elasticity, whereas train-of-four (TOF) monitoring measures muscle tone during neuromuscular blockades. This study investigated the relationship between muscle elasticity and tone during anesthesia induction using continuous SWE (C-SWE) and TOF monitoring. Methods: Fifteen patients who underwent general anesthesia with rocuronium were recruited. The muscle elasticity of the vastus lateralis was assessed using C-SWE, and muscle tone was evaluated using TOF monitoring. Measurements were taken at two time points: before rocuronium administration and during complete muscle relaxation, confirmed by the TOF ratio (TOF = 0). Statistical analyses were performed using paired t-tests and correlation analyses. Results: Data from 11 patients were analyzed. The mean shear wave velocity (SWV) decreased significantly from 5.0 ± 0.4 m/s before rocuronium administration to 3.1 ± 0.3 m/s during complete relaxation (p < 0.0001). A significant negative correlation was observed between the baseline SWV and the degree of reduction in the SWV (r = −0.728, p = 0.011). No significant correlations were found between SWV and demographic factors such as age, sex, height, or body mass index. Conclusions: C-SWE and TOF monitoring are reliable and sensitive methods for evaluating muscle elasticity and tone during general anesthesia. This study highlights the interplay between muscle tone and elasticity, suggesting that muscles with a higher baseline tone exhibit a greater reduction in elasticity after relaxation. These findings have implications for improving intraoperative muscle function assessments and advancing the application of C-SWE in clinical practice.